Cada um com sua luta: uma etnografia da relação entre sertanejos e mosquitos no alto sertão sergipano - Maia, Túllio Dias da Silva (2018)
The early years of the 20th century brought with it the discovery – perhaps the invention – of mosquitoes' ability to transmit pathogens. Occupying, since then, a highlighted space in medical literature, studies about these insects have always operated under the imperative of diseases' eradication – also the eradication of pathogens who entail such diseases. Echoing, nowadays, such occurrences, Northeastern Brazilian backwoods has become a target of an epidemiological investigation, withal after frequent cases of Zika fever in pregnant women and the vertical transmission to their babies causing them microcephaly, expressively in the backwoods of Paraíba and Pernambuco States (Brazil). This work constitutes an ethnography held in the surroundings of the Conservation Unity Natural Monument Grota do Angico (MONA), placed on the banks of São Francisco River, in Sergipe State, Brazil. Living together with a riverside family of fishermen for closely nonconsecutive 60 days, I held an ethnographic incursion, on the light of multispecies ethnography, approaching the relationships between sertanejos and mosquitoes. Native speech and practices, thus, led to insects as components of a caatinga that suffers and makes suffer. Their vector agency was pointed as features of only those mosquitoes from the cities, the latter, with their poisons and sewers. I propose, then, a more than vector approach for these insects in order to claim a mosquito ecology beyond the concerns historically related to them.